PENGARUH KEPEMILIKAN MANAGERIAL, KEPEMILIKAN INSTITUSIONAL, KEBIJAKAN HUTANG, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN - SISCA CHRISTIANTY DEWI (Jurnal Bisnis dan Akuntansi, 2008)
The research examines the effect of managerial ownership, institutional ownership, leverage policy,profitability, and firm size on dividend policy. The research model uses dividend policy to reflect the agency issues and conflict of interest between agent (manager) and principal (insider and outsider shareholders). Thirty two firms were used as sample listed at Jakarta Stock Exchange, and had positive earnings after tax and shared dividen from 2002 till 2005 repeatedly. Data were analyzed using multiple regression analysis. The results show that managerial ownership, institutional ownership, leverage policy, and profitability had a negative effect on dividend policy. The big firm would increase dividend policy rather than small firm.